Correlation of axial and radial breakdown dynamics in dielectric barrier discharges. (19th March 2018) - Höft, H; Becker, M M; Kettlitz, M
Abstract: Experimental studies of single-filament dielectric barrier discharges (DBDs) in a 0.1 vol% O2 in N2 gas mixture were performed with high spatial and temporal resolution. For the first time, the axial and radial dynamics and electrical characteristics of the DBDs were recorded by high-resolution imaging of the discharge emission combined with synchronised, fast electrical measurements. The axial propagation of the positive streamer and the radial expansion of the discharge channel were studied and correlated to each other. The analysis of the radial dynamics allowed the separation of the streamer propagation and the transient glow phase during channel formation. It was found that the discharge channel widens when the streamer hits the cathode surface and that both the diameter and the radial expansion velocities of the streamer increase with increasing axial propagation velocity. The synchronised quantification of the axial and radial streamer dynamics allowed the estimation of the electric field in the streamer head. Additionally, the time-resolved current density was determined by combining current measurements with fast imaging of the radial discharge development during streamer and glow phase.